Contribution of integrase inhibitor use, body mass index, physical activity and caloric intake to weight gain in people living with HIV - Giovanni Guaraldi; Jovana Milic; Elena Bacchi; Federica Carli; Marianna Menozzi; Iacopo Franconi; Alessandro Raimondi; Giacomo Ciusa; Valentina Masi; Michela Belli; Stefano Guaraldi; Emanuele Aprile; et al. (HIV Research & Clinical Practice)
Background: Integrase inhibitor (INSTI) use has been associated with greater weight gain (WG) among people living with HIV (PLWH), but it is unclear how this effect compares in magnitude to traditional risk factors for WG. We assessed the population attributable fractions (PAFs) of modifiable lifestyle factors and INSTI regimens in PLWH who experienced a ≥5% WG over follow-up. Methods: In an observational cohort study from 2007 to 2019 at Modena HIV Metabolic Clinic, Italy, ART-experienced but INSTI-naive PLWH were grouped as INSTI-switchers vs non-INSTI. Groups were matched for sex, age, baseline BMI and follow-up duration. Significant WG was defined as an increase of ≥5% from 1st visit weight over follow-up. PAFs and 95% CIs were estimated to quantify the proportion of the outcome that could be avoided if the risk factors were not present. Results: 118 PLWH switched to INSTI and 163 remained on current ART. Of 281 PLWH (74.3% males), mean follow-up was 4.2 years, age 50.3 years, median time since HIV diagnosis 17.8 years, CD4 cell count 630 cells/µL at baseline. PAF for weight gain was the greatest for high BMI (45%, 95% CI: 27–59, p < 0.001), followed by high CD4/CD8 ratio (41%, 21–57, p < 0.001) and lower physical activity (32%, 95% CI 5–52, p = 0.03). PAF was not significant for daily caloric intake (−1%, −9-13, p = 0.45), smoking cessation during follow-up (5%, 0–12, p = 0.10), INSTI switch (11%, −19-36; p = 0.34). Conclusions: WG in PLWH on ART is mostly influenced by pre-existing weight and low physical activity, rather than switch to INSTI.